2020
DOI: 10.1080/21645515.2020.1788300
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the induction of cellular immune responses by encapsulated and admixed archaeosome-based vaccine formulations

Abstract: Archaeosomes are liposomes formulated using total polar lipids (TPLs) or semi-synthetic glycolipids derived from archaea. Conventional archaeosomes with entrapped antigen exhibit robust adjuvant activity as demonstrated by increased antigen-specific humoral and cell-mediated responses and enhanced protective immunity in various murine infection and cancer models. However, antigen entrapment efficiency can vary greatly resulting in antigen loss during formulation and variable antigen:lipid ratios. In order to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 44 publications
(100 reference statements)
0
33
0
Order By: Relevance
“…Hailemichael et al also demonstrated that shorter-lived vaccine formulations preferentially induced T cell localization to the tumor and increased anti-tumor activity. SLA archaeosomes mediate a short-term depot effect on antigen of <48 h [ 18 ] while still stimulating strong and long-lasting cellular responses to a variety of antigens in preclinical models [ 13 , 14 ]. These properties have the potential to make it a more ideal partner for adjuvant combination strategies including TLR agonists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hailemichael et al also demonstrated that shorter-lived vaccine formulations preferentially induced T cell localization to the tumor and increased anti-tumor activity. SLA archaeosomes mediate a short-term depot effect on antigen of <48 h [ 18 ] while still stimulating strong and long-lasting cellular responses to a variety of antigens in preclinical models [ 13 , 14 ]. These properties have the potential to make it a more ideal partner for adjuvant combination strategies including TLR agonists.…”
Section: Resultsmentioning
confidence: 99%
“…Head-to-head comparative preclinical studies demonstrated that SLA was superior to a number of adjuvant types, including TLR agonists, in inducing antigen-specific T cell responses [ 17 ]. In mice, SLA has been shown to increase 1) antigen retention at the injection site, 2) immune cell recruitment, 3) antigen uptake, and 4) cytokine/chemokine expression [ 17 , 18 , 19 ]. Finally, SLA-based vaccine formulations can induce efficacious antigen-specific anti-tumor responses in a mouse melanoma model [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using OVA or HBsAg as antigens, we also demonstrated that SLA archaeosomes induce equivalent or superior antigen-specific immune responses to those obtained with many other adjuvants, including TLR3/4/9 agonists, oil-in-water and water-in-oil emulsions and aluminum hydroxide [ 15 ]. Initial studies indicated that SLA archaeosomes enhance immune cell infiltration, antigen retention and antigen uptake at the injection site [ 22 ]. However, no studies to date have evaluated the use of SLA archaeosomes, or to the best of our knowledge any other type of archaeosome, in combination with a panel of other types of adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most cationic liposomes used to deliver negatively charged nucleic acids, SLA archaeosomes are composed of a negatively charged lipid and hence are unlikely to bind to either CpG or Poly(I:C) directly. However, while it is unlikely that CpG or Poly(I:C) would interact with archaeosomes based on charge, it cannot be ruled out that the presence of archaeosomes could impact adjuvant distribution as has been shown previously for antigens [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation